2018
DOI: 10.2174/1568026618666180821144704
|View full text |Cite
|
Sign up to set email alerts
|

The Importance of the Structural Similarity of Drugs Used for Depression and Inflammation, Two Comorbid Diseases

Abstract: Growing evidence links inflammation to depression and the combination of antiinflammatory drugs with an antidepressant to treat depressive symptoms is currently suggested. There are only few studies concerning the molecular mechanism underlying this comorbidity, and many of them point out the importance of the tryptophan pathway. There is yet no data that analyzes the structural similarity of the molecules used for the treatment of these comorbid diseases. This review aimed first to classify current antidepres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…The anti-diabetic drug, metformin, also has neuroprotective effects via activation of antioxidant and anti-inflammatory pathways [81]. Since antidepressants share common molecular mechanisms with anti-inflammatory drugs [82], these common mechanisms appear to be the basis for the ability of antidepressants to protect against neurodegeneration [83]. Given that TBI is a risk factor for depression [84] and TBI patients with depression are treated with antidepressant drugs, we speculate that the recovery of the TBI patients treated with antidepressants may be attributed, in part, to the anti-inflammatory effects of these drugs [85].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-diabetic drug, metformin, also has neuroprotective effects via activation of antioxidant and anti-inflammatory pathways [81]. Since antidepressants share common molecular mechanisms with anti-inflammatory drugs [82], these common mechanisms appear to be the basis for the ability of antidepressants to protect against neurodegeneration [83]. Given that TBI is a risk factor for depression [84] and TBI patients with depression are treated with antidepressant drugs, we speculate that the recovery of the TBI patients treated with antidepressants may be attributed, in part, to the anti-inflammatory effects of these drugs [85].…”
Section: Discussionmentioning
confidence: 99%
“…The potential for anti-inflammatory drugs to have antidepressant effects is part of the evidence put forward by proponents of immunopsychiatry: “Randomized controlled studies using anti-inflammatories for depression have shown therapeutic effects [105]” [2] (p. 198). Finally, structural similarities between antidepressants affecting serotonin signaling (agomelatine, duloxetine and vortioxetine) and non-steroidal anti-inflammatory drugs (NSAIDs: Diclofenac, ketoprofen, naproxen and nabumetone) have recently been pointed out [106]. This thus would provide a structural basis for the claims that NSAIDS have antidepressant effects and antidepressants anti-inflammatory effects.…”
Section: Antidepressants and Anti-inflammatory Drugs May Not Be “Smentioning
confidence: 99%
“…Recent studies have shown the role of inflammatory mechanisms [1][2][3][4] and autoimmune mechanisms in the onset of psychiatric symptoms, such as depression [5][6][7]. In this sense, structural similarities have been identified between anti-inflammatory drugs and some antidepressants [8].…”
Section: Introductionmentioning
confidence: 99%